Energy trading model for multi-microgrid energy storage alliance based on Nash negotiation - Qiao, Huiting; Wu, Liangzheng; Wen, Shangyong; Zhang, Jigang (Frontiers in Energy Research, 2023)
With the continuous development of the electricity market and the gradual expansion of the number and scale of participation in market transactions, the traditional energy trading model has limited the formation of a competitive pattern of multi-agents. In this paper, a new multi-microgrid energy storage alliance energy trading model based on Nash negotiation is proposed. This model takes energy storage, multi-microgrid, and superior power grid enterprises as the main participants and establishes an energy market trading model with “buy–sell” cooperation and competition coexisting within the alliance based on Nash negotiation theory. Through the interaction of electricity between different entities, energy conversion and complementary utilization are increased, achieving reasonable allocation of resources, enhancing the overall flexibility of the alliance, and promoting the local consumption of a high proportion of new energy. The simulation results of the example show that the energy trading model based on Nash negotiation can fully leverage the initiative of demand-side participation in scheduling and improve the utilization rate of energy storage systems while ensuring the payment benefits of all participating entities, which can provide technical support for energy complementarity among multiple entities and provide new technological paths for the sustainable development of energy sharing mechanisms.